Problematic of languages In the translation of animal science terms - I Gusti Agung Istri Aryani; I Nengah Sudipa; Ida Bagus Putra Yadnya; Ni Made Dhanawaty (e-Journal of Linguistics, 2019)
Animal science terms have their specialty in scientific works because the differentresults of translation from the source language (SL) and target language (TL) can give effect tothe meaning. A translator should understand the terms in both languages to be able to considerthe problems and finding equivalence of terms for the result of the product. Problematic oflanguages may occur not only in SL but can be on both sides, SL and TL when the translator isnot the native speaker of the language. This study aims at finding problems of languagetranslation for animal science terms and finding the equivalence of terms using English as SLand Indonesian as TL. Qualitative method used in analyzing the data with a description of themeaning of terms in their translation within the direct interview information. Majorly, problemsfound in TL but also SL and TL which affected the meaning of animal science terms. Differentlexical choices of terms findings in the translation gave the effect of ambiguity andmisunderstanding to the scientists as target readers, however, the solution was given in order tohave an equivalence of understanding. It can be concluded that problematic of languages in bothlanguages should be considered for improvement in translation.